L'acqua: risorsa e minaccia a gestione delle risorse idriche e delle inondazioni in Europa (XIV-XIX secolo) - Bini, Elisabetta; Carnevale, Diego; Cecere, Domenico (Clio. Essays in History, Archaeology and Art History, 2023)
Every civilization has developed different forms of knowledge and techniques to manage and exploit water, an essential element for human life, but also to defend itself from the threats that can derive from it. In preindustrial times, the need to manage such a precious commodity led to the development of different technologies, the construction of infrastructures, the creation of special judiciaries, but it also fuelled conflicts between subjects who claimed privileged or exclusive access to water resources. In addition, the risks posed by the proximity of waterways or lake basins often led societies to develop prevention techniques and practices. This range of issues is at the heart of the essays collected in this volume, which examine various medium and large cities located in Central Western Europe - from the Rhine Valley to the Iberian Peninsula, from Paris to Palermo - between the fourteenth and the nineteenth centuries.